Nessie Judge's YouTube Crime Content and Anxiety Level of University of North Sumatra Students - Sianipar, Thessa Anabel; Munzaimah (Talenta Publisher, 2023)
This study aims to determine the extent and how much influence the criminal content of YouTube Nessie Judge on the anxiety level of University of North Sumatra students and how the anxiety level of University of North Sumatra students who watch criminal content YouTube Nessie Judge based on the Hamilton Anxiety Rating Scale (HARS). Correlational quantitative research methods using the theory of uses and effects. The population of this study were students of the University of North Sumatra amounted to 38,841 people with a sample of 100 respondents. This study uses quota sampling technique. Data collection technique is done using a questionnaire in the form of Google Form (G-Form). Researchers perform a series of data analysis techniques, namely descriptive statistical analysis and inferential statistical analysis. The results obtained that the level of anxiety students of the University of North Sumatra with no anxiety category as many as 33 respondents (33%), mild anxiety as many as 42 respondents (42%), moderate anxiety as many as 20 respondents (20%), and severe anxiety as many as 5 respondents (5%). From the hypothesis test results obtained rho value of 0.581 is on a scale of 0.41-0.70 which shows there is a significant relationship between the influence of criminal content YouTube Nessie Judge on the level of anxiety of students of the University of North Sumatra and give the effect of 34% based on the calculation of the determination test.